Cracking the code of hatchery-based mass production of mola (Amblypharyngodon mola) seed for nutritionsensitive aquaculture - Rajts, Francois; Dubey, Sourabh Kumar; Gogoi, Kalpajit; Das, Rashmi Ranjan; Biswal, Saurava Kumar; Padiyar, Arun Panemangalore; Rajendran, Suresh; Thilsted, Shakuntala H.; Mohan, Chadag Vishnumurthy; Belton, Ben (Frontiers Media, 2023)
Introduction: Small indigenous fish species (SIS) can be particularly rich in micronutrients and make a crucial contribution toward improving human nutrition. The introduction of mola (Amblypharyngodon mola), an SIS, which is particularly rich in vitamin A, into smallholder carp aquaculture systems has been widely promoted over the past decade as a promising nutrition-sensitive innovation. However, standardized techniques for the hatchery mass production of mola do not yet exist. We hypothesized that the lack of commercial hatchery mass-production techniques for mola seed is the key barrier limiting potential for widespread adoption of carp–SIS polyculture. Methods: To address this gap, we conducted breeding trials at a private hatchery in Odisha, India, from July to September 2022, to identify standardized methods for the hatchery-based mass production of mola seed. Breeding was induced using a synthetic gonadotropin-releasing hormone analog (SGnRHa) at 0.5 mL and 0.25 mL per kg of body weight of female fish and male fish, respectively. Fish spawned in double hapas in breeding tanks. Results: The average fertilization, spawning, and hatching rates over 10 breeding cycles were 81%, 82%, and 85%, respectively. A total of 8.5 million fertilized eggs and 6.4 million hatchlings were produced. The survival of fry during larval rearing trials at a stocking rate of 500 hatchlings/m2 was 58% after 22 days. The mola hatchlings and fry were sold to 29 farmers at prices comparable to those of Indian major carp. Discussion: This article makes a unique contribution to the literature by documenting the entire process of hatchery-based mass mola seed production, including broodfish collection and maintenance, hormone dose optimization, breeding arrangements, breeder characteristics, breeding behavior and performance fecundity, larval rearing, and seed sales to farmers. This information is intended to serve as a protocol to be followed by any individual or institution with an interest in mola breeding and represents an important contribution to the development of nutrition-sensitive aquaculture.